(untitled) (Lex localis - Journal of Local Self-Government, 2025)
The cumulative global emphasis on environmental sustainability has pushed enterprises to integrate green investments into their strategic frameworks. Hence, this study examines the factors persuading enterprises’ intentions to adopt green energy solutions, focusing on economic, organizational, and regulatory factors. Using a binary logistic regression model, the research analysesthe data from 365 enterprises of hilly states of India. The findings reveal that key operational focus and awareness significantly drive green investment decisions, whereas outmoded enterprise characteristics, such as tenure, industry type, and ownership structure, display weaker influence on the adoption of green practices. Despite the rising interest in green investments, high financial risks, long payback periods, and regulatory uncertainties remain the critical barriers. The study further underscores the need for targeted policy interventions, financial incentives, and increased awareness programs to accelerate green adoption. The insights added for this study can help policymakers and industry leaders develop tailored strategies to foster sustainable business practices, ensuring a balanced approach to economic growth and environmental conservation.